Cancer Stem Cells in Glioblastoma Multiforme - Bradshaw, Amy; Wickremesekera, Agadha; Brasch, Helen D.; Chibnall, Alice M.; Davis, Paul F.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2016)
Aim To identify and characterize cancer stem cells (CSC) in glioblastoma multiforme (GBM). Methods Four-micrometer thick formalin-fixed paraffin-embedded GBM samples from six patients underwent 3,3-diaminobenzidine (DAB) and immunofluorescent (IF) immunohistochemical (IHC) staining for the embryonic stem cell (ESC) markers NANOG, OCT4, SALL4, SOX2, and pSTAT3. IF IHC staining was performed to demonstrate co-expression of these markers with GFAP. The protein expression and the transcriptional activities of the genes encoding NANOG, OCT4, SOX2, SALL4, and STAT3 were investigated using Western blotting (WB) and NanoString gene expression analysis, respectively. Results DAB and IF IHC staining demonstrated the presence of a CSC population expressing NANOG, OCT4, SOX2, SALL4, and pSTAT3 with the almost ubiquitous presence of SOX2 and a relatively low abundance of OCT4, within GBM. The expression of NANOG, SOX2 and, pSTAT3 but, not OCT and SALL4, was confirmed by WB. NanoString gene analysis demonstrated transcriptional activation of NANOG, OCT4, SALL4, STAT3, and SOX2 in GBM. Conclusion This study demonstrated a population of CSCs within GBM characterized by the expression of the CSC markers NANOG, SALL4, SOX2, pSTAT3 and OCT4 at the protein and mRNA levels. The almost ubiquitous presence of SOX2 and a relatively low abundance of OCT4 would support the putative existence of a stem cell hierarchy within GBM.